Positive rumination can (also) interfere with sleep: A study in a non-clinical sample - Hairston, Ilana S.; Portal, Lilach; Carmon, Tal (Frontiers in Psychiatry, 2022)
It is postulated that negative ruminations perpetuate insomnia symptoms by increasing arousal. Less is known about the role of positive rumination. In this study, we set out to test the association between positive and negative ruminations and insomnia symptoms, in a non-clinical sample, asking whether reappraisal and suppression moderate the relationship between rumination types and symptoms of insomnia. Methods: A convenience sample of 354 participants (59% women), ages 18–50, responded to online questionnaires regarding symptoms of insomnia (Insomnia Severity Index [ISI]), Emotion Regulation Questionnaire that provides separate scales for Reappraisal and Suppression, Negative Rumination (Ruminative Response Scale), Positive Rumination and Dampening (Responses to Positive Affect questionnaire), and general health and demographics. Results: About 30% of respondents had moderate to severe symptoms of insomnia according to the ISI. The primary hypothesis was tested using three moderation models, where rumination type, emotion regulation styles, and interaction terms were predictors, and ISI scores were the outcome variable. Negative rumination positively predicted ISI (β=0.56, p<.001), while the interaction terms with Reappraisal (β=0.02, p=0.575) and Suppression (β=0.07, p=0.092) were not significant. Dampening also positively predicted ISI (β=0.56, p<.001), with the interaction term with Reappraisal (β=-0.09, p=0.060) nearly significant, but not with Suppression (β=0.08, p=.098). Positive rumination negatively predicted ISI (β=-0.12, p=.021), this relationship was reversed with emotion regulation factors in the model (β=0.11, p=.094), where the interaction with Reappraisal (β=0.13, p=.020) and Suppression (β=-0.13, p=.024) were both significant. Discussion: Positive Rumination weakly and negatively correlated with ISI, but the combination with Reappraisal was associated with more insomnia symptoms. By contrast, Dampening was more similar to negative rumination, associated with more insomnia symptoms, with minimal to no moderating effects. These observations are interpreted in the context of the role of emotion regulation strategies and sleep, and their potential clinical implications.